Pengembangan Lembar Kerja Geometri Transformasi Sebagai Asesmen Kemampuan Kognitif Mahasiswa berdasarkan RECCE-MODEL - Emma Aidha Yasmine; Anis Farida Jamil; Arif Hidayatul Khusna (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
Abstract:The application of real-life problems to Students’ Worksheet in learning transformation geometry makes learning meaningful. This is done in this study by developing Students’ Worksheet using a RECCE-MODEL framework. This research uses research and development type. The 3D model used in this study contains three stages, namely the understanding stage, the manufacturing stage, and the development stage. This study uses a student response questionnaire sheet, validation sheet, and the results of students’ worksheet work as research instruments. From the research results, the students’ worksheet developed was declared valid with a percentage of 79%, practical with a percentage of 85%, and effective by grouping students' cognitive abilities based on the RECCE-MODEL. Thus, it can be concluded that the transformation geometry worksheet developed can measure the cognitive abilities of students. Abstrak:Penerapan LKM geometri transformasi dalam kehidupan nyata menjadikan pembelajaran matematika lebih bermakna. Hal ini dilakukan pada penelitian ini dengan mengembangkan LKM menggunakan kerangka berpikir RECCE-MODEL. Penelitian ini merupakan penelitian pengembangan dengan model 3D yaitu Define (tahap pengertian), Design (tahap pembuatan), dan Develop (tahap pengembangan). Penelitian ini menggunakan lembar angket respon mahasiswa, lembar validasi, dan hasil pengerjaan LKM sebagai instrumen penelitian. Dari hasil penelitian, LKM yang dikembangkan dinyatakan valid dengan persentase 79%, praktis dengan persentase 85%, dan efektif dengan pengelompokkan kemampuan kognitif mahasiswa berdasarkan RECCE-MODEL. Sehingga dapat disimpulkan bahwa lembar kerja geometri transformasi yang dikembangkan dapat mengukur kemampuan kognitif mahasiswa.